Pengaturan Ruang Terbuka Hijau Berdasarkan Peraturan Daerah Kota Denpasar Nomor 27 Tahun 2011 - Ni Putu Feggy Cintya Karna; I Ketut Sukadana; I Nyoman Sutama (Jurnal Interpretasi Hukum, 2020)
In this era, urban areas have become a problem that is quite difficult to overcome, especially in the matter of utilization of green open space caused by land demand continuing to increase. The problems discussed in this study are the coverage of green open space and the legal consequences of constructing buildings in green open space in the city of Denpasar. The type of the research used in this study is normative legal research with two types of sources of legal materials, primary and secondary. Data collection was carried out using a literature study which was then analyzed qualitatively. The results show that green open spaces in cities belong to the spaces in the form of areas or paths dominated by plants functioning as protection of certain habitats, city facilities, infrastructure safety networks, and/or agricultural cultivation as regulated in Regional Regulation of Denpasar City Number 27 of 2011 concerning the Spatial Planning for the City of Denpasar in 2011-2031. Furthermore, the legal consequences for violations of erecting buildings in green open spaces or controlling spatial use of urban areas are in the form of administrative sanctions for supervision activities which result in obstruction of the implementation of the spatial utilization program, both carried out by the permit recipient and the licensor. Types of administrative sanctions for the community consist of warnings and/or reprimands, temporary suspension of administrative services, temporary suspension of development activities and/or use of space, revocation of permits relating to spatial use, restoration of functions or rehabilitation of spatial functions, demolition of buildings not in accordance with the plan spatial planning, licensing/whitening, and the imposition of fines. There are also other sanctions in the form of imprisonment for a maximum of 6 (six) months or a maximum fine of IDR. 50,000,000.00, - (fifty million rupiah).